The regulatory roles of B cell subsets in transplantation. (1st February 2018) - Chu, Zhulang; Zou, Weilong; Xu, Yanan; Sun, Qiquan; Zhao, Yong
ABSTRACT: Introduction : B cells mediate allograft rejection through antigen presentation, and production of cytokines and antibodies. More and more immunosuppressive agents specifically targeting B cells and plasma cells have been applied in clinical transplantation. However, recent studies have indicated the regulatory roles of B cells. Therefore, it is vital to clarify the different effects of B cell subsets in organ transplantation so that we can completely understand the diverse functions of B cells in transplantation. Areas covered : This review focuses on the regulatory roles of B cells in transplantation. B cell subsets with immune modulation and factors mediating immunosuppressive functions of regulatory B (Breg) cells were analyzed. Therapies targeting B cells and the application of B cells for transplant tolerance induction were discussed. Expert commentary : Besides involving rejection, B cells could also play regulatory roles in transplantation. Breg cells and the related markers may be used to predict the immune tolerant state in transplant recipients. New therapeutic strategies targeting B cells should be explored to promote tolerance induction with less impact on the host's protective immunity in organ transplanted patients.